Currículo da vida: contribuições Freireanas para o ensino da Matemática - Morais, Rogério de (Universidade Federal de São Carlos, 2019)
The school curriculum lies in an arena of disputes involving cultural, ideological and power relations and is characterized by its non-neutrality. In this study, the objective was to analyze the potential of intervention and transformation of reality through the teaching practice, in the area of mathematics, of a Freirean critical curriculum. A systematic review on the teaching of mathematics in the EJA was developed, based on a survey of knowledge production in the thesis and dissertation database of CAPES. An action research was started with the students of the project "Readers of the World", in the municipality of Conchas, São Paulo, aiming to construct with them a new curriculum of the teaching of Mathematics, in the Education of Young and Adults, that starts from the contradictions perceived in the moments of dialogue between educator and students and using the theoretical-methodological referential of historical and dialectical materialism mainly through the authors Freire and Caraça. The initial results show that few works have been interested in the theme of confluence between mathematical education, youth and adult education, and the liberating pedagogy of Paulo Freire, and so far research has proved to be fruitful and full of potentialities. scientific knowledge can serve as a fact for the emancipation of the subjects of learning, since it is used to overcome the contradictions of the inhuman reality that mediates the subjects in a gnosiological situation.
Life curriculum: Freirean contributions to teaching Mathematics
Keywords: Educação Matemática; Educação de Jovens e Adultos; Currículo; Educação Libertadora; Emancipação; Emancipation; Liberating Education; Curriculum; Youth and Adult Education; Mathematics Education; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO